Praktek Berbangsa Dan Bernegara Berdasarkan Ketuhanan Di Indonesia Dalam Kaitanya Dengan Teori Pembentukan Negara Teokrasi - Riyanto Riyanto; Avi Firzashafira; Taufiqurrohman Syahuri (International Forum of Researchers and Lecturers, 2024)
Pancasila as a national ideology implies a religious view of the nation, which upholds the values of God Almighty. This is as determined in the constitution of the Republic of Indonesia, which is stated in Article 29 A paragraph (1) of the 1945 Constitution as a result of the amendment of Chapter XI which states that